NZ J Ecol 2017
DOI: 10.20417/nzjecol.41.22
|View full text |Cite
|
Sign up to set email alerts
|

Aerial glyphosate application reduces grey willow (Salix cinerea) canopy cover, increases light availability, and stimulates kahikatea (Dacrycarpus dacrydioides) growth

Abstract: Grey willow (Salix cinerea) is widely established in New Zealand's remaining swamps and fens, and in many areas has replaced endemic kahikatea (Dacrycarpus dacrydioides) forest. Conservation managers need to know how to restore willow-invaded wetlands to a resilient natural state, but knowledge on how to achieve this goal is limited. We planted kahikatea seedlings into an intact stand of grey willow and into areas where the herbicides glyphosate or triclopyr had been aerially applied to control willow ~1.5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Results were more equivocal however in greenhouse studies where 2–30% shade cloths were used to approximate the range of light levels found within a podocarp forest. Griffiths and McAlpine (2017) found improved growth of saplings of Kahikatea when light levels were increased under a willow canopy from 28 to 64% of full sunlight after herbicide treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were more equivocal however in greenhouse studies where 2–30% shade cloths were used to approximate the range of light levels found within a podocarp forest. Griffiths and McAlpine (2017) found improved growth of saplings of Kahikatea when light levels were increased under a willow canopy from 28 to 64% of full sunlight after herbicide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the risk of damage from falling willows, Kahikatea saplings in the FULL treatment areas did continue to grow, as did those in the MANUAL treatment, where a light well had been cut within the partially damaged willow canopy. Maintenance of canopy conditions equivalent to our PARTIAL treatments over extended periods is likely to be challenging to achieve using broad spectrum herbicides such as glyphosate, but may be possible using more frequent applications of suitably selective herbicides such as triclopyr (Champion et al 2011; Griffiths & McAlpine 2017), precision application of herbicides by “intelligent” automated drones (Librán‐Embid et al 2020), or other approaches such as selective biological control agents (Harman 2004; Adair et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Effective strategies may vary between swamp and fen zones or between sites due to differences in plant community structure and composition. These could include the following: re‐introducing Kahikatea to swamp zones after control (Griffiths & McAlpine ) as they grow much taller than Grey Willow and produce a dense canopy that is likely to inhibit Grey Willow establishment due to shading (Champion ; Niinemets & Valladares ); applying control over larger areas and aligning treatment boundaries with barriers to Grey Willow seed dispersal (such as grazed farmland or areas of continuous forest) to slow Grey Willow re‐establishment by seed; and identifying dicot‐selective herbicides that could provide effective control of scattered Grey Willow with minimal nontarget impacts in monocot‐dominated fen areas. Assessing the cost‐effectiveness of additional targeted or aerial boom‐spray control of surviving and reinvading Grey Willow would also be a useful line of enquiry (Griffiths et al .…”
Section: Discussionmentioning
confidence: 99%
“…The largest populations are located at low elevation (<500 m) near original planting sites (Champion 1994). But, Grey Willow is spreading rapidly by wind-dispersed seed and, once established, can form dense monospecific stands that can alter ecosystem composition, structure and function (Champion 1994;Cremer 2003;Coleman 2010;Watts et al 2012;Griffiths & McAlpine 2017). Dense Grey Willow stands may also impede regeneration of the endemic tree species Kahikatea (Dacrycarpus dacrydioides (A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation